Validation of a Modified Pediatric Risk of Mortality III Model in a Pediatric Intensive Care Unit in Thailand - Kanokpan Ruangnapa; Sittikiat Sucheewakul; Tippawan Liabsuetrakul; Edward McNeil; Kantara Lim; Wanaporn Anantaseree (Pediatric Respirology and Critical Care Medicine)
Objective: The objective of this study is to compare the performance of a modified Pediatric Risk of Mortality (PRISM) III model with the original PRISM III in prediction of mortality risk in a Thailand pediatric intensive care unit (PICU). Subjects and Methods: Children aged 1 month to 18 years who stayed in the PICU for more than 8 h during November 2013 to December 2016 were included in the study. Results: The medical records of 1175 PICU patients were included in the analysis. The patients were randomly split into two equal groups: a development (n = 588) and a validation (n = 587) sample. A modified PRISM III model was derived from the original PRISM III by omitting arterial blood gas parameters and adding selected clinical variables. The model was developed using a multiple logistic regression model on the development sample and assessed using the area under the curve (AUC) obtained from a receiver operating characteristic curve. The modified PRISM III scores were significantly higher in nonsurvivors (median = 9, interquartile range [IQR] = 4 − 13) compared to survivors (median = 2, IQR = 0 − 5). The modified PRISM III model had similar discriminative performances compared to the original PRISM III in predicting 2-day mortality (AUC: 0.874 vs. 0.873), 7-day mortality (AUC: 0.851 vs. 0.851) and overall mortality (AUC: 0.845 vs. 0.956). The modified PRISM III model was calibrated in the validation sample, and the standardized mortality ratios (SMRs) were similar. Conclusions: The performance of a modified PRISM III model in predicting mortality risk was comparable to the original PRISM III. Both had similar discriminative performance and SMR for overall mortality prediction in a PICU.